2010
DOI: 10.1111/j.1462-2920.2010.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression‐based identification of genetic determinants of the bacterial symbiosis ‘Chlorochromatium aggregatum

Abstract: SummaryThe phototrophic consortium 'Chlorochromatium aggregatum' is a highly structured association of green sulfur bacterial epibionts surrounding a central, motile bacterium and is the most specific symbiosis currently known between two phylogenetically distinct bacterial species. Genes and gene products potentially involved in the symbiotic interaction were identified on the genomic, transcriptomic and proteomic level. As compared with the 11 available genomes of free-living relatives, only 186 open reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…From this initial reconstruction, only 382 reactions remained after manual curation (Supplementary Material 1). As mentioned above, several enzymes related to amino acid and nitrogen metabolism change their expression profile between free-living and symbiotic states (Wenter et al, 2010). To better understand the metabolic changes related to both states, we selected those reactions belonging to amino acid metabolism for further EFM analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From this initial reconstruction, only 382 reactions remained after manual curation (Supplementary Material 1). As mentioned above, several enzymes related to amino acid and nitrogen metabolism change their expression profile between free-living and symbiotic states (Wenter et al, 2010). To better understand the metabolic changes related to both states, we selected those reactions belonging to amino acid metabolism for further EFM analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data showed that GS was present only in symbiosis (Wenter et al, 2010). Accordingly, the motifs obtained with ACoM-c software showed that the EFMs were clearly different in hotspots of NH 3 assimilation between symbiotic and free-living states (Figure 2).…”
Section: Metabolic Analysis Of Chlorobium Chlorochromatii D Cerqueda-mentioning
confidence: 99%
See 3 more Smart Citations